PENGARUH ENVIRONMENTAL SOSIAL GOVERNANCE DISCLOSURE DAN INTELLECTUAL CAPITAL TERHADAP PROFITABILITY (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Septi Lillahsari Sulistyorini; Rousilita Suhendah (Universitas Sarjanawiyata Tamansiswa, 2026)
The aim of this research is to analyze how the influence of Environmental, Social, Governance (ESG) Disclosure and Intellectual Capital (IC) influences the increase profitability the data used in this study is secondary data from manufacturing companies listed on the Indonesian Stock Exchange (IDX) in 2022-2024. The sample was selected using the random sampling method purposive sampling and the data obtained amounted to 36 companies. The data was processed using software Eviews version 13. The results obtained from this study are Environmental, Social, Governance (ESG) Disclosure does not have a significant effect on profitability However Intellectual Capital (IC)has a significant impact on profitability. The implications of these findings suggest that manufacturing companies need to focus more on managing Intellectual Capital as a key driver of profitability, as well as re-evaluating ESG disclosure strategies to ensure they have a tangible impact on the company's financial performance.